The Impact of Business Ethics on Organizational Performance: An Exploratory Study in a Number of Colleges Working at the University of Mosul - Hussein, Adhwaa (The Arab Journal of Administration, 2020)
The recent administrative changes have received wide attention by decision makers in all organizations as a result of the rapid changes of high competition, increased globalization, administrative corruption, etc., which put organizations in a moral bind. All these and other factors have led organizations to pay attention to the ethics of management, For the great role played by this ethics in organizational performance and its direct contributions to improving its work and acquiring the personnel who have expertise and skills which enhances its performance and competitive position in the market. To identify and know the role and impact of the ethics of administrative work in organizational performance / exploratory study in a number of colleges of the University of Mosul and by trying to answer the following questions: 1- Do the research faculties rely primarily on administrative work ethics? 2- What is the nature of the relationship between the ethics of administrative work and organizational performance in the faculties of inquiry? 3- Does the ethics of administrative work affect morally in the organizational performance of the faculties in question? In order to answer these questions, a number of hypotheses were tested using a number of statistical methods of data obtained from the subjects using a questionnaire prepared according to the theoretical aspect of the research that was prepared in advance. Because of the lack of interest in the training programs that it conducts in this area, while these led the researcher to present a number of proposals, perhaps the most prominent interest in the establishment of training courses and benefit from the results of research conducted in A field Valokhalakiet is a gain for organizations in the long run.